Theoretical Grounds of Identification of the Essence of the Enterprise Development Efficiency Category - Adzhavenko Maryna M. (Bìznes Inform, 2014)
Modern economic conditions put a new problem in front of scientists, namely: capability of an enterprise to survive in the unfavourable external environment. This problem is a system and complex one and its solution is within the plane of management of capital, personnel, development, efficiency, etc. The article marks out that efficiency is a corner stone of the modern economic science, which justifies studies of the gnoseological essence of the efficiency category. The main goal of the article lies in the study of scientific and theoretical grounds of formation of the enterprise development efficiency under modern conditions of the changing internal and external environments. The other goals of the article are identification of the essence of the development efficiency category, deepening the theoretical foundation of assessment of efficiency of enterprise development in the modern economic science. The article conducts an ontological analysis of the essence and goals of the enterprise development efficiency notion, studies evolution of scientific approaches and systemises theoretical provisions of the specified category and their assessment in the economic science. In the result of the study the article identifies a new vector of theoretical grounds and dominating logic of formation of the methodology of assessment of efficiency of enterprises under conditions of innovation development of the state, namely: it underlines principles of systemacy, complexity, self-organisation, significance of human capital as an important factor of increase of efficiency and development. Development of methodological grounds of assessment of efficiency of enterprise innovation development is a prospective direction of further studies.